Transitional justice from the margins: Collective reparations and Tunisia's Truth and Dignity Commission. (April 2022) - Robins, Simon; Gready, Paul; Aloui, Ahmed; Andrieu, Kora; Ben Hamza, Hajer; Ferchichi, Wahid
Abstract: The Tunisian revolution of 2011 moved from socio-economic to political concerns, and from the margins and periphery of the South and West of the country to the centre, Tunis, driven by the slogan of "jobs, dignity and freedom". The goal of this article is to understand the potential of using the spatially informed concept of marginalisation to reimagine transitional justice, using the "victim zone" as a case study. The Truth and Dignity Commission's founding legislation tasked it with identifying victim zones that had "suffered systematic marginalisation or exclusion" and proposing reparation for structural violations suffered. Empirical data collected from two disadvantaged regions of Tunisia are used to provide a bottom-up, victim-centred, look at structural and economic violence. The IVD has largely failed to-date to deliver on its promise in relation to collective reparations, but a combination of theory and empirical data provides a springboard for a discussion of how the margins could unsettle current transitional justice practice, both normatively and practically. The article concludes by outlining an unfinished business agenda for Tunisia and implications for future transitional justice. Specifically, it argues for a transitional justice from the margins that focuses on space as well as time, collectives as well as individuals, a normative plurality rather than a single universalised global framework, decentralised agency rather than centralised institutional primacy, and a new social contract (forms of participation and recognition) rather than the continuity of elite bargains.